Aplicación del proceso enfermero a la práctica asistencial en el caso clínico de crisis asmática - González Godoy, Andrea Carolina (2013)
The nursing process as the target of the NANDA International, is to strengthen the development of nursing knowledge. The type of study is descriptive, prospective and qualitative. The methodology was applied to a 6 years 8 months old physician diagnosed of Asthmatic Crisis. The present study aims to use the nursing process to diagnose using NANDA International taxonomy and NOC and NIC linkages that guide the identification and implementation of nursing actions. In this context, nursing diagnoses, which guided and nursing interventions that were rated by NOC outcomes were determined. So are nursing diagnoses: Risk of infection (code 00004), Risk for impaired physical activity (code00094), Social isolation (code 00053), The role of caregiver fatigue (code 00061), Ineffective planning activities (code 00199), Impaired Dentition (code 00048), Delayed growth and development (code 00111); who guide the NOC results are: Risk control: infectious process ( código1924), Knowledge: prescribed activity (código1811), Alterations lifestyle of the primary caregiver (código0116), Participation in games (code 2203), Oral hygiene (código1211), Anxiety level (código1100), Child development: 5 years (código0108); to guide the results of a nursing intervention. Concluding that the pattern is more affected valuation pattern 8 Rol- Relations. KEYWORDS Nursing Process, Asthmatic Crisis, Healthcare Practice.